MANAJEMEN PEMBELAJARAN PASRAMAN SAD DHARMA DWIJENDRA DI YAYASAN DHARMA LAKSANA MATARAM - Widyatmaja, Wayan; Zaenab, Siti (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
This study aims to conduct a study of the learning management of the Pasraman Sad Dharma Dwijendra Mataran at the Dharma Laksana Foundation.This research was conducted using qualitative methods with descriptive data analysis. Data collection techniques used in this study were non-participatory observation techniques, structured and unstructured interview techniques, and documentation. The data obtained is then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. To check the validity of the data using credibility, transferability, dependability, and confirmability. Based on the results of the study, four findings were foud, namely 1). Lesson plans prepared by the teacher or Acarya include attendance, learning materials, learning models, strategies and methods, facilities and infrastructure, media, planning evaluation and paying attention to thr preparation of student or Brahmacari2). The organization of learning carried out by the teacher or Acarya includes organizing the learning schedule, organizing learning haours, organizing classes, organizing learning materials and resources, as well as organizing student or Brahmacari, 3). The implementation of learning carried out by the teacher or Acarya includes three stages, namely the preliminary activity stage, the core activity stage, the final learning activity stage; 4). The form of supervision or evaluation carried out by the teacher or Acarya is using practical methods, direct observation, and giving test orally and in writing to measure and know the skills and understanding of student or Brahmacari towards learning material.